2021
DOI: 10.1007/s40894-021-00172-3
|View full text |Cite
|
Sign up to set email alerts
|

E-Mentoring to Address Youth Health: A Systematic Review

Abstract: Electronic mentoring (e-mentoring), the integration of digital technology in mentoring relationships, has recently grown in popularity; however, the effectiveness of e-mentoring in addressing youth health has not been synthesized to date. The current study synthesizes the literature on e-mentoring to affect the health and well-being of youth (10–24 years) through a systematic review and evidence quality assessment. A total of 833 records were identified, of which 14 met eligibility criteria (published in Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…This scoping review provides an overview of the existing evidence base regarding the ways in which adults may be influenced by the experience of mentoring children and adolescents in programs designed for this purpose, the methods used in these studies, and characteristics of the mentors and programs involved which evidence has been : 37,38,39;Jumpstreet: 85,90;Nebraska Human Resource Initative: 8,34,35,47,59,83;PERACH: 25,28;Young Women's Leadership Program: 49,58,50,55,60. gathered. The review complements existing syntheses of mentoring research (e.g., DuBois et al, 2002;Kaufman et al, 2021;Raposa et al, 2019) as the first systematic synthesis to the authors' knowledge of research on how adult mentors may be influenced by formal youth mentoring. In the following sections, we consider our findings by research question, identify gaps in the existing evidence base, and provide suggestions for future research.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This scoping review provides an overview of the existing evidence base regarding the ways in which adults may be influenced by the experience of mentoring children and adolescents in programs designed for this purpose, the methods used in these studies, and characteristics of the mentors and programs involved which evidence has been : 37,38,39;Jumpstreet: 85,90;Nebraska Human Resource Initative: 8,34,35,47,59,83;PERACH: 25,28;Young Women's Leadership Program: 49,58,50,55,60. gathered. The review complements existing syntheses of mentoring research (e.g., DuBois et al, 2002;Kaufman et al, 2021;Raposa et al, 2019) as the first systematic synthesis to the authors' knowledge of research on how adult mentors may be influenced by formal youth mentoring. In the following sections, we consider our findings by research question, identify gaps in the existing evidence base, and provide suggestions for future research.…”
Section: Discussionmentioning
confidence: 95%
“…Numerous meta‐analyses (e.g., DuBois et al, 2002; DuBois et al, 2011; Raposa et al, 2019; Tolan et al, 2014) and systematic reviews (e.g., Kaufman et al, 2021; Sanchez et al, 2018) have synthesized evidence of the impact of mentoring programs on the outcomes of participating youth mentees. Moreover, research has explored the experiences of youth serving as mentors in cross‐age peer mentoring relationships with younger youth (Karcher, 2009; Karcher & Berger, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, e‐mentoring programs have mostly targeted special populations of youth (Kaufman et al, 2021) and focused on supporting youth with health conditions or creating educational and vocational opportunities for underrepresented groups (Shpigelman, 2014). Research has shown that such programs can successfully improve youth health outcomes (Ahola Kohut et al, 2018; Cassiani, 2017; Gregg et al, 2017; Kaufman, Levine, et al, 2022; Lindsay et al, 2018, 2019; Shpigelman & Gill, 2013; Stinson et al, 2016), and effectively increase the participation rates of girls in science, technology, engineering, and mathematics (STEM) (O'Connor et al, 2018; Stoeger et al, 2013, 2019, 2021). Research on a virtual mentoring program that matches adolescents with chronic illness with young adults with the same illness found mentors described the ways that their participation in the program helped them to grow as a person and develop skills and build self‐confidence (Ahola Kohut et al, 2017).…”
Section: E‐mentoringmentioning
confidence: 99%
“…The majority of these studies focused on youth with pre‐existing health conditions rather than promoting overall health. The e‐mentoring programs targeted youth subpopulations facing challenges using in‐person mentoring, highlighting the potential for e‐mentoring to support youth with unique health concerns during their transition to adulthood (Kaufman et al, 2022). Recent research has indicated that participation by at‐risk youth in an online intervention program that combines physical activity mentoring and interpersonal connections is associated with improved resiliency, social support, and psychological distress (Glaser et al, 2022).…”
Section: Introductionmentioning
confidence: 99%